Hierarchical tube brush-like Co3S4@NiCo-LDH on Ni foam as a bifunctional electrocatalyst for overall water splitting. (5th August 2021) - Xu, Xiaohu; Su, Le; Zhang, Yujie; Dong, Lijuan; Miao, Xiangyang
Abstract : The Co3 S4 @NiCo-LDH/NF nanocomposite exhibits outstanding electrocatalytic performances toward both the HER and OER at high current densities, along with a remarkable durability. Abstract : With the popularization of the concept of green development, hydrogen energy as an ideal energy carrier has been paid more and more attention. Electrochemical water splitting as one of the most effective means of hydrogen production has aroused wide interest. The development of high-activity and low-cost bifunctional electrocatalysts for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) plays a key role in hydrogen production via water splitting. Herein, hierarchical tube brush-like Co3 S4 @NiCo-LDH nanoarrays in situ grown on Ni foam were successfully synthesized via a three-step hydrothermal strategy. The as-fabricated catalyst exhibits simultaneously outstanding electrocatalytic performances for both the HER (overpotentials of 210 and 251 mV at 50 and 100 mA cm −2, respectively) and the OER (overpotentials of 262 and 320 mV at 100 and 300 mA cm −2, respectively) in 1 M KOH electrolyte. Impressively, the Co3 S4 @NiCo-LDH electrode presents a remarkable stability up to 100 h for the OER and HER at a high current density of 100 mA cm −2 . Furthermore, by employing the Co3 S4 @NiCo-LDH as both the cathode and anode for overall water splitting (OWS), a low cell voltage of 1.59 V is required to deliver the current density of 10 mA cm −2, along with a remarkable durability. The superior electrocatalytic activity may be attributed to the following: (1) the in situ growth on the Ni foam substrate can not only improve structural stability and conductivity but also endow faster charge transfer as well as bubble release; (2) its peculiar structure provides large active surface areas, more accessible surface active sites and fast charge/mass transport; (3) the prominent synergistic effect between Co3 S4 and NiCo-LDH justifies the excellent electrocatalytic activity for the HER and OER. This work will provide a novel idea for constructing effective bifunctional catalysts for hydrogen production via OWS.